A New Platform of B/N‐Doped Cyclophanes: Access to a π‐Conjugated Block‐Type B3N3 Macrocycle with Strong Dipole Moment and Unique Optoelectronic Properties. (19th March 2022) - Li, Pengfei; Shimoyama, Daisuke; Zhang, Niu; Jia, Yawei; Hu, Guofei; Li, Chenglong; Yin, Xiaodong; Wang, Nan; Jäkle, Frieder; Chen, Pangkuan
Abstract: We herein describe a new design principle to achieve B/N‐doped cyclophane where an electron‐donor block of three triarylamines (Ar3 N) and an acceptor block of three triarylboranes (Ar3 B) are spatially separated on opposite sides of the π‐extended ring system. DFT computations revealed the distinct electronic structure of the block ‐type macrocycle MC‐ b ‐B3N3 with a greatly enhanced dipole moment and reduced HOMO–LUMO energy gap in comparison to its analogue with alternating B and N sites, MC‐ alt ‐B3N3 . The unique arrangement of borane acceptor Ar3 B and amine donor Ar3 N components in MC‐ b ‐B3N3 induces exceptionally strong intramolecular charge transfer in the excited state, which is reflected in a largely red‐shifted luminescence at 612 nm in solution. The respective linear open‐chain oligomer L‐ b ‐B3N3 was also synthesized for comparison. Our new approach to donor–acceptor macrocycles offers important fundamental insights and opens up a new avenue to unique optoelectronic materials. Abstract : An unusual block ‐type π‐conjugated macrocycle MC ‐ b ‐B3N3 that shows a strong dipole moment and a narrow HOMO–LUMO gap is introduced. Compared with other cyclic hexamers, its unique orientation of electron‐donor block and acceptor block resulted in largely red‐shifted orange emission both in solution and in the solid state.